Impact of fuel energy prices in Tunisia - Lassaad Jebali; Anis Kacem (International Journal of Energetica)
The policy of subsidizing petroleum derivatives in Tunisia distorts the real prices of goods and services. It does not take care on environment. There is no serious fiscal policies to reduce pollution generated by energy products.The calculation of the correlation matrix between different macroeconomic aggregates does not give a negative effect of oil prices on national GDP. However, this result is serious, because the impact on economic (performance) is hidden, affecting first the general level of prices, unemployment and inflation. Instability of oil prices has no apparent impact. This fact and instability make many difficulties to manage prices and inflation after revolution. Impact on GDP passes through Economic Vulnerability Indicator (EVI) and agricultural sector.